2D and 3D Crystal Formation of 2, 6‐Bis[4‐ethylphenyl]anthracene with Isotropic High Charge‐Carrier Mobility. (30th October 2017) - He, Chao; Li, Aiyuan; Yan, Lijia; Zhang, Dongwei; Zhu, Yanan; Chen, Haibiao; Meng, Hong; Goto, Osamu
Abstract: Organic semiconductor materials with high charge‐carrier mobility and high luminescence are promising for fabricating high‐performance organic light‐emitting transistors and electrically pumped organic laser diodes. Some derivatives with an anthracene core show both characteristics; however, independently controlling the size and the thickness of single‐crystal films is challenging. Here, 2D and 3D crystal formation is demonstrated by using an air‐stable organic semiconductor, 2, 6‐bis[4‐ethylphenyl]anthracene (BEPAnt). The shape of the single‐crystal films can be changed from about 0.10 mm in diameter and 400 nm in thickness to 1.0 mm in diameter and 50 nm in thickness by controlling the growth conditions using saturation–supersaturation vapor pressure curves. The in‐plane growth rate increases by ten times while the out‐of‐plane growth rate decreases to about 1/8 as the growth temperature increases from 210 to 250 °C. Single‐crystal organic field‐effect transistors based on BEPAnt show isotropic mobilities as high as 7.2 cm 2 V −1 s −1 . Abstract : The shape of single‐crystal films of 2, 6‐bis[4‐ethylphenyl]anthracene can be changed from about 0.10 mm in diameter and 400 nm in thickness to 1.0 mm in diameter and 50 nm in thickness by controlling the growth conditions using saturation–supersaturation vapor pressure curves. The fabricated single‐crystal OFETs show isotropic mobilities as high as 7.2 cm 2 V –1 s –1 .